Pengaruh Servant Leadership, Organizational Commitment Terhadap Employee Performance Serta Work Life Balance Sebagai Mediator Pada Universitas Pelita Bangsa - Ida Komala; Dea Nursifa; Siti Khodijah; Ahmad Mardhotillah; Retno Purwani Setyaningrum (DPPM Universitas Pelita Bangsa, 2023)
The purpose of this study was to examine and analyze the influence of servant leadership on employee performance mediated by organizational commitment and moderated by work life balance at Pelita Bangsa University. This research method uses quantitative analysis, however, to strengthen the research results, researchers use descriptive qualitative analysis,. The sample of respondents in the study was 100 using the SMART PLS method. The results of the study concluded that 1) servant leadership has a positive and significant effect on employee performance. 2) Servant leadership has a positive and significant effect on employee performance, 3) Servant leadership has a positive and significant effect on organizational commitment, 4) Servant leadership has an effect on employee performance through work life balance as a mediator. Based on these findings, it is evident that the Servant Leadership leadership style is appropriate because it has an effect on increasing employee performance, similarly organizational commitment is also appropriate for use because it further supports the relationship between servant leadership on employee performance, but work life balance still does not support increased employee performance, this is due bearing in mind that Pelita Bangsa University should continue to improve the work life balance of employee performance so that there is more balance between employee performance and employee personal life.